2014
DOI: 10.1007/s00018-014-1760-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms and functional implications of polarized actin remodeling at the T cell immunological synapse

Abstract: Transient, specialized cell-cell interactions play a central role in leukocyte function by enabling specific intercellular communication in the context of a highly dynamic systems level response. The dramatic structural changes required for the formation of these contacts are driven by rapid and precise cytoskeletal remodeling events. In recent years, the immunological synapse that forms between a T lymphocyte and its antigen-presenting target cell has emerged as an important model system for understanding imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 190 publications
(267 reference statements)
0
61
0
Order By: Relevance
“…F-actin accumulates in the periphery of the IS and is depleted from the center, forming a stereotyped annular pattern (Le Floc'h and Huse, 2015). Lytic granules cluster beneath the center of the F-actin ring, and it has been proposed that they release their contents primarily by fusing with the actin-free plasma membrane in this region (Stinchcombe and Griffiths, 2007; Stinchcombe et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…F-actin accumulates in the periphery of the IS and is depleted from the center, forming a stereotyped annular pattern (Le Floc'h and Huse, 2015). Lytic granules cluster beneath the center of the F-actin ring, and it has been proposed that they release their contents primarily by fusing with the actin-free plasma membrane in this region (Stinchcombe and Griffiths, 2007; Stinchcombe et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…IS formation also involves intense remodeling of filamentous actin (F-actin), which controls both the growth and the organization of the interface (Le Floc'h and Huse, 2015). Recently, we demonstrated that phosphoinositide 3-kinase (PI3K) activity stimulates actin polymerization within the IS by recruiting Dock2, an exchange factor for the Rho GTPase Rac (Le Floc'h et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we showed that the lamellipodial-like dSMAC and lamella-like pSMAC exhibit distinct rates of inward actin flow and that the rates of centripetal TCR MC movement across these two zones matched their distinct actin flow rates (Yi et al, 2012). Nevertheless, the existence of these arcs has been questioned (Beemiller and Krummel, 2013;Le Floc'h and Huse, 2015), and they have never been observed in primary T cells. Moreover, an alternate mechanism to drive TCR MC movement across the pSMAC has been proposed that involves dynein-dependent, microtubule-based transport (Hashimoto-Tane et al, 2011).…”
Section: Introductionmentioning
confidence: 90%
“…The F-actin within the dSMAC undergoes robust retrograde flow, driven both by actin polymerization at the leading edge and myosin-based contractility, which drives clusters of antigen receptors and integrins toward the center of the contact (Hammer and Burkhardt, 2013, Le Floc'h and Huse, 2015). Concurrently, bursts of anterograde flow originate at the IS and propagate to the back of the cell (Ritter et al, 2015).…”
Section: Immune Synapses Are Mechanically Activementioning
confidence: 99%